Strategy for Resolving Problematic Financing Using Restructuring Methods Through Ta'awun Principles at Bank Syariah Indonesia Magetan 2 - Nirma Wulandari; Yunaita Rahmawati (Mutanaqishah: Journal of Islamic Banking, 2023)
Financing is one of the activities in the banking world that can be enjoyed by the public. In the process of carrying out every banking transaction activity, of course, there will be problems that occur. Financing problems that often occur include credit or installment problems made by customers, known as NPF. This research aims to analyze the causes of NPF, analyze the handling of NPF, and analyze the impact of NPF, as well as the impact of handling NPF using restructuring through the ta'awun principle on the Bank and customers. This research uses a descriptive qualitative approach. The results of this research show that the causes of problematic financing consist of several factors, namely the customer's poor character and disasters or misfortunes that befall the customer. The restructuring mechanism through the ta'awun method at BSI KCP Magetan 2 was carried out using a directed procedure. The positive impacts of implementing the restructuring method are (a) maintaining customer trust in the bank; (b) the bank has a good reputation; and (c) restructuring is considered to have saved financing problems that might otherwise occur. The negative impacts are (a) making the bank must do work repeatedly. Because the financing that had been distributed to customers experienced a bottleneck, the bank had to carry out investigations with customers to find out what happened.